Advancing Embedded Systems Education: A Pedagogical Programming Framework for Smart System and Control Applications - Benyeogor, Mbadiwe S.; Andrew O. Benyeogor; Kabiru A. Olaiya; Prosper Agumey (SPC Journal of Education, 2024)
This article introduces a pedagogical framework incorporating a curriculum and conceptual examples, specifically tailored to the need of embedded systems technology instructors The curriculum covers crucial subjects such as hardware and software fundamentals, programming languages, sensors integration, motion control, and their practical applications. It emphasizes hands-on training, project-based learning, and problem-solving to foster a holistic understanding of embedded systems. The curriculum is designed to cater to embedded systems training centers globally, addressing the growing demand for skilled professionals in areas such as robotics, telecommunications, automation, and microprocessor engineering. It aims to bridge the skills gap, empower trainers, and equip students with the necessary competencies to thrive in the evolving field of robotics and programming. Overall, this curriculum serves as a valuable resource for instructors, enabling them to enhance their teaching methods and contribute to the advancement of embedded systems and STEM education.